Igneous petroleum systems in the Malargüe fold and thrust belt, Río Grande Valley area, Neuquén Basin, Argentina. (January 2020) - Spacapan, J.B.; D'Odorico, A.; Palma, O.; Galland, O.; Rojas Vera, E.; Ruiz, R.; Leanza, H.A.; Medialdea, A.; Manceda, R.
Abstract: The Río Grande Valley (Neuquén Basin, Argentina) is a large oil field where voluminous igneous sill complexes are emplaced in different levels of the sedimentary sequence in a fold and thrust belt setting. These sills are predominantly emplaced in organic-rich units such as Vaca Muerta and Agrio Formations and are critical elements of the defined petroleum system, as they affect the thermal maturity of the surrounding source rocks, and also act as naturally fractured reservoirs. In this contribution, we integrated structural sections, borehole data, core descriptions, petrophysical laboratory tests and organic geochemistry measurements to characterize the impact of the magmatism in the petroleum system of the Río Grande Valley oil field. Especially, we focused in evaluating the impact of the sill-complexes in hydrocarbon generation, migration and accumulation. Our data shows that: (1) intrusions are preferably emplaced in organic rich units; (2) a large number of intrusions is observed in areas intensely deformed by imbricated thrusts; (3) an increase in the number of intrusions drives stronger and more extensive maturation processes in the Vaca Muerta formation, enhancing notably the cracking of kerogen to hydrocarbon within this unit; (4) where the number of intrusions increases, the concentration of total gas and methane also increases, given that all sills are suitable reservoirs; (5) igneous rocks provide a low resistance path for fluids flow and act as the main reservoirs in the study area; (6) the reservoir quality of igneous intrusions is dominated by the combination of matrix and fracture framework properties; (7) zeolites are the most common type of cement in these reservoirs; (8) deep sills located in the Vaca Muerta formation produce larger volumes of hydrocarbons relative to shallower intrusive reservoirs. The Río Grande Valley oil field offers a world-class example of the implications of igneous complexes in hydrocarbon generation, migration and accumulation in a compressive tectonic setting of fold and thrust belt. Highlights: Commercial oil production from magmatic intrusions reservoirs. Theoretical model of an atypical igneous petroleum system in a fold and thrust belt. Thermal impact of sill-complexes has positive implications on petroleum systems. Porosity, permeability and capillary pressure tests for magmatic intrusions reservoirs.